1989
DOI: 10.1002/1097-0142(19891101)64:9<1922::aid-cncr2820640927>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Cell kinetics and hormonal receptor status in inflammatory breast carcinoma. Comparison with locally advanced disease

Abstract: The biological and prognostic role of hormone receptor status and proliferative activity have been studied in two series of patients affected by inflammatory breast carcinoma (IBC, 28 patients) and locally advanced breast cancer (LABC, 50 patients). Estrogen receptor (ER) and progesterone receptor (PgR) were measured by dextran-coated charcoal (DCC) method whereas proliferative activity was measured by 3H-thymidine autoradiographic labeling index (LI). The percentages of E R f and P g R f cases resulted lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 19 publications
2
28
0
Order By: Relevance
“…In our series, PR-negative status and ER-and PR-negative status were significantly associated with poor OS as previously reported. 32,33 On multivariate analysis, the strongest prognostic factor was the delivery of HDC with HSCS. Patients who received HDC experienced longer DFS and OS than did patients receiving conventional doses.…”
Section: Resultsmentioning
confidence: 99%
“…In our series, PR-negative status and ER-and PR-negative status were significantly associated with poor OS as previously reported. 32,33 On multivariate analysis, the strongest prognostic factor was the delivery of HDC with HSCS. Patients who received HDC experienced longer DFS and OS than did patients receiving conventional doses.…”
Section: Resultsmentioning
confidence: 99%
“…MKI67 encodes Ki-67 antigen, a large protein of unknown function that is a classical histopathological marker associated with cell proliferation. Paradiso et al (19) have reported higher proliferative activity (mesuared by [ 3 H]thymidine autoradiographic labeling index) in IBC than in non-IBC.…”
Section: Discussionmentioning
confidence: 99%
“…IBC is more likely to be hormone receptornegative and HER-2/neu tumor marker-positive than noninflammatory LABC. [24][25][26] Despite improved outcomes due to multimodality therapy for BC in general, survival of women with IBC (5-year survival 41%, median survival 2.9 years) is worse than for LABC (63%, 6.4 years, respectively).…”
Section: Molecular Characteristics Of Ibcmentioning
confidence: 42%